Turning Resistance into Passion for Knowledge with the Tools of Agency: Teaching-Learning about Theories of Evolution for social justice among foster youth - Eduardo Vianna; Anna Stetsenko (Perspectiva)
We discuss implementing critical-theoretical pedagogy within a collaborative transformative project in a foster care program in the U.S. to showcase the activist role of the educator in providing tools of agency for youth struggling against oppression. This project aimed at enhancing and spurring the residents’ (adolescent boys’) agency through collaborative learning activities. The cornerstone was to explore the ethical-political dimensions of knowledge in connection with the boys’ own thematic universe, thus compelling them to take a stand on social and scientific issues in their own lives, their communities, and the society at large. The topic of evolution was chosen to critically examine erroneous and nefarious assumptions associated with a reductionist version of evolutionary theory that promotes the fallacious and racist, and quite widespread, view that race-based social inequality is biologically determined. This was a view that some boys apparently took up from social discourses and practices in their surrounds. A workshop on evolution led by the first author provided a forum for the boys to discuss their views on such contentious matters as social ranking and presumed inequalities in human potential while confronting outrageous stereotypes about so called “Black inferiority” and whether notions of evolution and human nature support or challenge such views.